Morphometric and flow cytometric analysis of small cell undifferentiated carcinoma of the bladder. Issue 10 (October 1989) - Blomjous, C E; Vos, W; Schipper, N W; De Voogt, H J; Baak, J P; Meijer, C J
Abstract : Eighteen cases of primary small cell carcinoma of the bladder were studied. Three patients survived for two years and one survived for five years, which was significantly worse when compared with poorly differentiated transitional cell carcinoma (WHO grade 3). Aggressive tumour behaviour was independent of the presence of neuroendocrine characteristics. Morphometric analysis showed that the nuclear size, which was comparable with that reported in pulmonary small cell carcinoma, was significantly smaller than in poorly differentiated transitional cell carcinoma. Nuclear morphometry may therefore help identify small cell bladder carcinoma, especially in the absence of neuroendocrine differentiation characteristics. DNA flow cytometry of paraffin wax embedded specimens showed aneuploidy in 14 tumours--five were peritetraploid and two multiple aneuploid--and only three were diploid. Aggressiveness of small cell bladder carcinoma usually coincides with aneuploidy in most cases, but diploid tumours may also follow a rapid, lethal clinical course.